Tinjauan Fiqh Muamalah Terhadap Jual Beli Ball (Borongan) di Pasar Sumpang Kota Parepare - B, Asfiani; Budiman; Aris; Mujahidah Annisa (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2023)
Low prices with good quality and high public interest in used clothes are the reasons for the rise of traders at Sumpang Market, Parepare City. Used goods bought by the seller wrapped in sacks are called claws (cap sack). This research is a qualitative research with a descriptive method, namely in-depth research covering all that occurs in the field and the type of research used is field research. Data collection using in-depth interviews, observation, documentation and literature study. The results of the study concluded that the background to the implementation of buying and selling used clothes at the Sumpang Market in Parepare City was because the prices of used clothes were cheap with good quality and the interest of the people of Parepare City in used clothes was relatively high. The practice of buying and selling used clothes at the Sumpang Market in Parepare City, namely traders selecting used clothes from sacks, and separating clothes that are still decent. The marketing strategy uses promotions on social media accounts (Instagram, Facebook and Whatsapp accounts). According to Fiqh Muamalah, there are 2 laws on buying and selling used clothes at the Sumpang Market, Parepare City, namely: The law of buying and selling traders with distributors (agents/importers) contains elements that are prohibited in Islam, namely tadlis (fraud) and gharar (uncertainty) because traders in carrying out transactions for buying used clothes with these distributors cannot find out the contents of the goods in the sacks ordered to the agent.